Linking patterns and processes in tree plant communities to conservation and management of the South American savannas : Vinculando padrões e processos em comunidades arbóreas ao planejamento e manejo da conservação de savanas da América do Sul - Maciel, Everton Alves (2020)
Orientador: Fernando Roberto Martins